Intelligent Emergency Vehicle Preemption Using A Density Based System - Anirudh, Voruganti; Neelaveni Ammal, M; Suryatej, Datla; V Satvik, A (International Journal of Engineering and Technology, 2018)
Transit by road is one of the crude methods of transportation in various parts of the world as of today. The abundance of vehicles utilizing the street is expanding in an ascending order consistently. Because to this reason, trafï¬c congestion in urban areas is becoming inescapable these days. The normal purpose behind trafï¬c blockage is because of poor trafï¬c prioritization, wherein a portion of the paths may have less trafï¬c than the others with measure up to signal light length for both the paths. This Inefï¬cient administration of trafï¬c leads to wastage of crucial time, contamination, wastage of fuel, expenditure of transportation and worry to drivers, and so on however more vitally emergency vehicles like rescue vehicle stall out in trafï¬c. Our project is on density based trafï¬c control with the need to prioritize vehicles like emergency vehicle and ï¬re brigade. In this way, it is especially important to plan a system to keep away from the setbacks. In this way counteracting mishaps, impacts, and trafï¬c jams.Â Â